A comparative evaluation of placebo effect on pain perception parameters in open-label versus double-blind groups: a prospective randomized pilot study in healthy volunteers - Bhargava, Shashikant; Sarangi, Sudhir Chandra; Kumar, Vijay L. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Considerable placebo response rate is commonly observed in placebo-controlled trials involving analgesics. However, there is paucity of evidence with regard to comparison of effect of open-label placebo versus double-blind placebo on pain perception. Methods: In this study, cold water maintained at 4±1°C was used to induce experimental pain. Enrolled subjects were randomized to receive either 2% lignocaine gel as active drug or K-Y jelly as placebo as per the groups in open-label (two groups) and double-blind (two groups) study. Pain perception was evaluated using pain threshold time and pain tolerance time after immersion of subject’s hand in the cold water. Pain intensity was assessed using visual analogue scale (VAS). Results: Sixty-nine subjects were randomized into 4 study groups namely open-label lignocaine (OLL; N=17), open-label placebo (OLP; N=18), double-blind lignocaine (DBL; N=17) and double-blind placebo (DBP; N=17). OLP application increased pain intensity on VAS from 67 (47, 84) to 72 (39, 88) mm (p=0.018). OLL application reduced pain perception pain threshold time from 20.4 (4.0, 45.1) to 24.1 (6.3, 124.2) seconds (p=0.049) and pain tolerance time from 32.7 (6.8, 110.2) to 40.0 (7.7, 156.7) seconds (p=0.019). The change in pain parameters (before and after application of study intervention) was comparable without any significant difference among the four study groups (p=0.257 for pain threshold time, p=0.165 for pain tolerance time and p=0.563 for pain intensity score). Conclusions: Lignocaine and placebo gel application showed comparable change in pain perception irrespective of blinding.